2018
DOI: 10.18535/ijmsci/v5i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Extraction Methods and Solvents on the Phenolic Composition and Antioxidant Activity of Silybum Marianum Leaves Extracts

Abstract: Objective: The objectives of this study were essentially to evaluate the best technique for extracting phenolic compounds from Silybum marianum leaves. Subjects and Methods: Two extraction methods (maceration and decoction), using four extraction solvents. The efficiency of the extraction methods was estimated by quantifying the total polyphenol contents by the Folin -Ciocalteu method and by determining the antioxidant power of the various extracts by the ability to trap the free radical DPPH °, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…populations were studied for chemical and productive properties by Sulas et al [19] reporting, in acetone/water leaves extract, a content of antioxidant capacity (7.6 mmol TEAC 100 g −1 DW) and total flavonoids (11.5 g CE kg −1 DW) lower than our results. A content of phenolic compounds lower (18.7 mg GAE g −1 DW) than our results was also reported by Benchaachoua et al [25] in a aqueous-methanol extract of leaves of S. marianum collected in Algeria. Ben Salem et al [26] found phenolic contents of artichoke (Cynara scolymus L.) leaves extracts from 39.9 to 54.5 mg GAE g −1 DW lower than our results.…”
Section: Antioxidant Capacity and Phenolic Contentsupporting
confidence: 60%
“…populations were studied for chemical and productive properties by Sulas et al [19] reporting, in acetone/water leaves extract, a content of antioxidant capacity (7.6 mmol TEAC 100 g −1 DW) and total flavonoids (11.5 g CE kg −1 DW) lower than our results. A content of phenolic compounds lower (18.7 mg GAE g −1 DW) than our results was also reported by Benchaachoua et al [25] in a aqueous-methanol extract of leaves of S. marianum collected in Algeria. Ben Salem et al [26] found phenolic contents of artichoke (Cynara scolymus L.) leaves extracts from 39.9 to 54.5 mg GAE g −1 DW lower than our results.…”
Section: Antioxidant Capacity and Phenolic Contentsupporting
confidence: 60%
“…The concentration of silymarin is organ-dependent, and it is only localized in the outer portion of the fruit, which includes all the cell layers from the pericarp epidermis to the albumen, and embryos [6], accounting for 1.5-4.3% of the fruit weight [7]. Silymarin is not present in flowers, stems, or leaves, and it is not found in steps before the development of fruit [8,9], which explains why other milk thistle plant organs have been scarcely investigated for bioactive compounds: total polyphenol and flavonoid contents in leaves' extracts were studied by Saidi, et al [10]; a phytochemical screening and gas chromatography-mass spectrometry (GC-MS) analysis of bioactive compounds present in ethanolic leaves extract was conducted by Mani, et al [11]; and Sulas, et al [12] studied the concentrations of crude protein, fat, total phenolics, and total flavonoids in leaves, heads, and stems.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture is then cooled to room temperature and the filtrate collection. Aqueous is a good solvent for the extraction of condensed tannins by decoction and maceration [32]. The decoction is very suitable for non-destroyed substances by the heat [31].…”
Section: Methods Of Decoctionmentioning
confidence: 99%